2016
DOI: 10.17116/terarkh201688798-103
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of myeloproliferative disease with t(8;13)(p11;q12) associated with eosinophilia and lymphadenopathy

Abstract: Myeloproliferative disease associated with FGFR1 rearrangement (8p11), which is included in the 2008 WHO Classification of Myeloid Neoplasms, is a rare and extremely aggressive abnormality. The paper describes a clinical case of a 39-year-old female patient who was detected to have leukocytosis (as high as 47.2·109/l), absolute eosinophilia (as high as 3.1·109/l), and enlarged peripheral lymph nodes during her visit to a doctor. The bone marrow (BM) showed the changes typically encountered in myeloproliferativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Patients carrying the t(8;22)(p11;q11) and the subsequent BCR-FGFR1 fusion gene follow an aggressive course. There are a few reported patients who have been treated unsuccessfully with hydroxyurea [6], chemotherapy or TKIs [2, 5]. More potent TKIs, such as ponatinib which exhibits pan-FGFR inhibitory activity, may be of clinical benefit [10, 11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients carrying the t(8;22)(p11;q11) and the subsequent BCR-FGFR1 fusion gene follow an aggressive course. There are a few reported patients who have been treated unsuccessfully with hydroxyurea [6], chemotherapy or TKIs [2, 5]. More potent TKIs, such as ponatinib which exhibits pan-FGFR inhibitory activity, may be of clinical benefit [10, 11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MPN with a t(8;22) translocation and a chimeric BCR-FGFR1 fusion gene either present or rapidly transform into an acute leukaemia [3, 4], usually refractory to currently available chemotherapeutic regimens including tyrosine kinase inhibitors (TKIs) [2, 5]. No consensus on management is available for this condition.…”
Section: Introductionmentioning
confidence: 99%